Intracellular complement − the complosome − in immune cell regulation. (September 2017) - Arbore, Giuseppina; Kemper, Claudia; Kolev, Martin
Highlights: Recent, evidence have demonstrated presence of intracellular complement proteins and their activation (the complosome). The complosome plays a role in basic cell processes such as metabolism. The interaction between the complosome and intracellular pathogens needs to be further elucidated. Abstract: The complement system was defined over a century ago based on its ability to "complement" the antibody-mediated and cell-mediated immune responses against pathogens. Today our understanding of this ancient part of innate immunity has changed substantially and we know now that complement plays an undisputed pivotal role in the regulation of both innate and adaptive immunity. The complement system consists of over 50 blood-circulating, cell-surface expressed and intracellular proteins. It is key in the recognition and elimination of invading pathogens, also in the removal of self-derived danger such as apoptotic cells, and it supports innate immune responses and the initiation of the general inflammatory reactions. The long prevailing classic view of complement was that of a serum-operative danger sensor and first line of defence system, however, recent experimental and clinical evidences have demonstrated that "local" tissue and surprisingly intracellular complement (the complosome) activation impacts on normal cell physiology. This review will focus on novel aspects of intracellular complement activation and its unexpected roles in basic cell processes such as metabolism. We also discuss what the existence of the complosome potentially means for how the host handles intracellular pathogens such as viruses.